RATIFIKASI INTERNATIONAL CONVENTION ON THE PROTECTION OF THE RIGHTS OF ALL MIGRANT WORKERS AND MEMBERS OF THEIR FAMILIESDAN UPAYA PERLINDUNGAN TENAGA KERJA INDONESIA - Masnun, Leolita; Wijayani, Erly (Jurnal Masyarakat dan Budaya, 2010)
Indonesian Migrant Worker (Tenaga Kerja Indonesia/TKI) still encouter many problems throughout their migration phases, from departure, placement, to returning phase. Although the government of Indonesia has issued several regulations in order to protect TKI, yet, the cases of violation are still increasing. Some people argue that the legal instruments to protect the TKIare inadequate because the government of Indonesiahas still not ratified the International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families. This article discusses the importance of the Convention to protect Indonesian Migrant Worker. Keyword: ratification, International Convention on the Protection of the Right of All Migrant Workers & Members of Their Families, Indonesian Migrant Worker (TKI)